Effect of triazophos on mitotic activity and chromosomal behavior in root meristems of Allium cepa L. - Pandey, Archana; Sakya, Shyam R (Botanica Orientalis: Journal of Plant Science, 2010)
Effect of triazophos (an organophosphorous insecticide) on mitotic activity and chromosomal behavior in the meristematic region of root tip cells of Allium cepa L. was assessed. The insecticide showed mitotic depression and positive chromo-toxic effects. Abnormalities, such as stickiness, plasmolysed cells, equatorial plate shifting, polar shifting, irregular chromosome arrangement, precocious arms formation, bridge formation, C-metaphase, fragmentation of chromosomes, unequal cytokinesis, diagonal cytokinesis, delayed cytokinesis and formation of binucleated cells, were recorded in the chemically pretreated root meristem. Key-words: chromosomal and cellular abnormalities; cytotoxic effect; mitotic index; phase indices. DOI: 10.3126/botor.v6i0.2903 Botanica Orientalis - Journal of Plant Science (2009) 6: 4-7